Modified glass powder for front silver paste of solar cell and its preparation method and application

By covering the Ni-P alloy coating on the surface of the glass powder, the instability problem of glass frit during the printing process is solved, and the bonding strength between the silver electrode of the solar cell and the conversion efficiency of the battery is improved.

CN115394469BActive Publication Date: 2025-02-14CHANGZHOU JUHE NEW MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211136911.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-19
Publication Date
2025-02-14
Estimated Expiration
2042-09-19

AI Technical Summary

Technical Problem

In the process of solar cell manufacturing, the prior art is difficult to ensure the stability of glass frit during long-term printing friction shearing, which affects the bonding strength between silver electrodes and silicon wafers and the conversion efficiency of the battery.

Method used

The surface of the glass powder is coated with Ni-P alloy plating by electroless plating, and a modified glass powder is prepared for silver paste on the front of the solar cell. The method includes placing the glass powder in a plating solution of nickel salt, reducing agent, complexing agent and stabilizer, stirring and reacting at 90°C for 1.5 h to form a stable Ni-P alloy plating layer.

Benefits of technology

Modified glass powder improves the viscosity stability of the slurry, reduces the printing gate break ratio, enhances the bonding strength between the silver electrode and the silicon wafer, and increases the open circuit voltage and filling factor of the solar cell.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a modified glass powder for silver paste on the front side of a solar cell, and a preparation method and application thereof. The modified glass powder for silver paste on the front side of a solar cell comprises glass powder and a Ni-P alloy coating coated on the surface of the glass powder, wherein the Ni-P alloy coating is coated on the surface of the glass powder by chemical plating. The modified glass powder for silver paste on the front side of a solar cell provided by the present invention has excellent stability, and avoids the active groups on the surface of the glass directly contacting with the organic phase, thereby causing the deterioration and decomposition of the organic phase; at the same time, due to the high conductivity and high melting point of the coating, the electronic conductivity of the glass is increased, and the premature flow of the glass powder is suppressed, thereby reducing the degree of damage to the PN junction by the glass, and obtaining a higher open circuit voltage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of conductive paste for solar cells, and particularly relates to a modified glass powder for silver paste on the front side of solar cells, and a preparation method and application thereof. Background Art

[0002] my country's mineral energy resources are not abundant, but its solar energy resources are relatively abundant. More than two-thirds of the country's total area has sunshine hours greater than 2000 hours, and the annual radiation is 5000MJ / m 2 As mentioned above, photovoltaic power generation is an important new energy technology at present and in the next ten years. Its application prospects and market scale are huge, and among them, crystalline silicon solar cells occupy an absolute dominant position in the photovoltaic industry.

[0003] The operating principle of solar cells is based on the photovoltaic effect of semiconductors. When exposed to light, the charge distribution in the cell changes, generating an electromotive force and current. A solar cell is essentially a large-area diode, consisting of a PN junction, a passivation film, and metal electrodes. A boron source is doped on the n-type substrate, and a phosphorus source is doped on the p-type substrate, forming a p+ or n+ emitter, respectively, which then form a PN junction with the silicon substrate. This PN junction creates a built-in electric field, separating the carriers generated by light and collecting them on the front and back metal electrodes, respectively. During solar cell manufacturing, a metal paste is screen-printed onto a silicon wafer and then sintered to form contact electrodes. The light-receiving side of the solar cell uses silver paste as the metal electrode, low-melting-point glass as the bonding phase, and an organic material as the carrier. At a certain temperature, the organic matter in the paste evaporates, and the remaining glass frit accumulates on the surface of the anti-reflection coating, ablating the silicon nitride anti-reflection coating and undergoing a redox reaction with the silicon. The reduced lead metal in the glass is in liquid form, forming a Pb-Ag melt when it meets Ag. Because the glass frit corrodes the Si surface anisotropically, the reaction creates corrosion pits on the Si surface. A layer of glass forms between the silver and the N-type Si. At high temperatures, the glass sinks, carrying and dissolving some of the silver metal. During cooling, the lead and Ag in the paste separate, and the excess Si grows epitaxially on the silicon wafer. Ag particles precipitated from the glass grow randomly on the silicon wafer surface, crystallizing on the crystal faces and forming ohmic contacts with the Si surface. Although the glass frit only accounts for 1-5% of the silver paste mass, it directly affects the bond strength between the silver electrode and the silicon wafer, the solderability of the silver electrode, and the conversion efficiency of the battery. To ensure good ohmic contact between the printed and sintered electrode paste and the silicon substrate, while also ensuring the paste's stability during prolonged printing, friction, shear, and static storage, specialized treatment of the glass frit is crucial. Summary of the Invention

[0004] The main purpose of the present invention is to provide a modified glass powder for solar cell front silver paste and its preparation method and application, so as to overcome the shortcomings of the prior art.

[0005] To achieve the aforementioned object of the invention, the technical solutions adopted by the present invention include:

[0006] An embodiment of the present invention provides a modified glass powder for silver paste on the front side of a solar cell. The modified glass powder for silver paste on the front side of a solar cell comprises glass powder and a Ni-P alloy coating coated on the surface of the glass powder. The Ni-P alloy coating is coated on the surface of the glass powder by chemical plating.

[0007] The embodiment of the present invention further provides a method for preparing the aforementioned modified glass powder for the front silver paste of solar cells, which comprises:

[0008] The glass powder is placed in a plating solution containing a nickel salt, a reducing agent, a complexing agent and a stabilizer, and stirred at 90°C for a reaction for 1.5 hours. A Ni-P alloy coating is coated on the surface of the glass powder to prepare a modified glass powder for the front silver paste of a solar cell, wherein the pH value of the plating solution containing the nickel salt, the reducing agent, the complexing agent and the stabilizer is adjusted to 12 by adding ammonia water.

[0009] An embodiment of the present invention further provides a solar cell front silver paste, which includes the aforementioned modified glass powder for the solar cell front silver paste.

[0010] Compared with the prior art, the present invention has the following beneficial effects:

[0011] (1) The modified glass powder provided by the present invention prevents the active groups on the glass surface from contacting with the organic phase, greatly improves the viscosity stability of the slurry, and ensures the smoothness of the printing of the slurry during the screen printing process;

[0012] (2) The modified glass powder provided by the present invention can reduce the degree of damage to the PN junction of the silicon wafer, ensuring that the crystalline silicon solar cell has a higher open circuit voltage;

[0013] (3) The modified glass powder provided by the present invention has good electronic conductivity, and the resistance of photogenerated electrons transmitted from the silicon wafer to the silver electrode is smaller, ensuring that the solar cell has a good fill factor. DETAILED DESCRIPTION

[0014] In view of the shortcomings of the prior art, the inventors of this case, after long-term research and extensive practice, have proposed the technical solution of the present invention. The technical solution of the present invention will be clearly and completely described below. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by persons of ordinary skill in the art without making any creative effort shall fall within the scope of protection of the present invention.

[0015] Specifically, as one aspect of the technical solution of the present invention, a modified glass powder for silver paste on the front side of a solar cell comprises glass powder and a Ni-P alloy coating coated on the surface of the glass powder, wherein the Ni-P alloy coating is coated on the surface of the glass powder by chemical plating.

[0016] In some preferred embodiments, the glass powder is composed of three or more elements of Te, Pb, Bi, Li, Na, W, Si, Zn, Mo, Cu, Mg, Al, B, Ti, and Zr.

[0017] In some preferred embodiments, the glass powder includes the following components counted by molar percentage of oxides: 5-50% SiO2, 5-40% PbO, 0.5-10% CuO, 5-40% TeO2, 5-15% Bi2O3, 1-10% Li2O, 1-5% Na2O, 5-20% WO3, 1-10% ZnO, 1-10% MoO3 and 1-5% MgO.

[0018] In some preferred embodiments, the glass powder includes a skeleton support as a glass network structure and an intermediate and / or network modifier as a glass network structure; the skeleton support includes SiO2 and TeO2; the intermediate and / or network modifier includes PbO, CuO, Bi2O3, Li2O, Na2O, WO3, ZnO, MoO3 and MgO.

[0019] Specifically, a glass powder composed of three or more elements selected from Te, Pb, Bi, Li, Na, W, Si, Zn, Mo, Cu, and Mg is coated with a Ni-P alloy layer via chemical plating. The glass powder comprises, by mole percentage of oxides, 5-50% SiO2, 5-40% PbO, 0.5-10% CuO, 5-40% TeO2, 5-15% Bi2O3, 1-10% Li2O, 1-5% Na2O, 5-20% WO3, 1-10% ZnO, 1-10% MoO3, and 1-5% MgO. SiO and TeO2 serve as glass network formers and support the glass network structure, while the other oxides serve as intermediates or modifiers of the glass network. This glass powder modified by chemical plating has excellent stability, avoiding direct contact between the active groups on the glass surface and the organic phase, which may cause deterioration and decomposition of the organic phase; at the same time, due to the high conductivity and high melting point of the coating, the electronic conductivity of the glass is increased, while the premature flow of the glass powder is suppressed, the degree of damage to the pn junction by the glass is reduced, and a higher open-circuit voltage is obtained.

[0020] In some preferred embodiments, the content of the Ni-P alloy coating in the modified glass powder for the front silver paste of the solar cell is 0.5 to 5 wt %.

[0021] In some preferred embodiments, the content of P in the Ni-P alloy coating is 4-12 wt %.

[0022] Another aspect of the embodiments of the present invention further provides a method for preparing the aforementioned modified glass powder for the front silver paste of solar cells, comprising:

[0023] The glass powder is placed in a plating solution containing a nickel salt, a reducing agent, a complexing agent and a stabilizer, and stirred at 90°C for a reaction for 1.5 hours. A Ni-P alloy coating is coated on the surface of the glass powder to prepare a modified glass powder for the front silver paste of a solar cell, wherein the pH value of the plating solution containing the nickel salt, the reducing agent, the complexing agent and the stabilizer is adjusted to 12 by adding ammonia water.

[0024] In some preferred embodiments, the nickel salt includes nickel sulfate, but is not limited thereto.

[0025] In some preferred embodiments, the reducing agent includes sodium hypophosphite, but is not limited thereto.

[0026] In some preferred embodiments, the complexing agent includes sodium citrate, but is not limited thereto.

[0027] In some preferred embodiments, the stabilizer includes thiourea, but is not limited thereto.

[0028] In some preferred embodiments, the concentration of the nickel salt in the plating solution comprising the nickel salt, the reducing agent, the complexing agent and the stabilizer is 0.05 to 0.5 mol / L.

[0029] Furthermore, the molar ratio of the reducing agent to the nickel salt is 2 to 8:1.

[0030] Furthermore, the mass ratio of the stabilizer to the nickel salt is 0.5 to 2:100.

[0031] Furthermore, the mass ratio of the complexing agent to the nickel salt is 3 to 10:100.

[0032] Furthermore, the mass ratio of the glass powder to the nickel salt is 2.2 to 3.5:1.

[0033] In some more specific embodiments, the method for preparing the modified glass powder for the front silver paste of solar cells includes:

[0034] The surface modification of glass powder is completed by chemical reduction reaction of sodium hypophosphite and nickel sulfate, in which nickel sulfate is the main salt, providing the Ni required in the chemical plating reaction process. 2+, is the source of nickel in the coating; sodium hypophosphite is a reducing agent and the main component of chemical nickel plating. It can provide the electrons required to reduce nickel ions and convert Ni 2+ Reduction to elemental nickel. Furthermore, sodium citrate and thiourea are required during the electroless plating process. Sodium citrate complexes the nickel ions in the plating solution, significantly reducing the amount of free nickel ions. Thiourea acts as a stabilizer, preferentially adsorbing on the surface of the glass frit to inhibit the intense autocatalytic reaction that produces a large amount of Ni-P black powder and the spontaneous decomposition of the plating solution, thereby stabilizing the plating solution and allowing the electroless plating process to proceed smoothly. The concentration of the nickel sulfate plating solution is 0.05-0.5 mol / L. Too high a concentration will result in larger Ni-P alloy particles during the electroless plating process, while too low a concentration will slow the reaction or even prevent it from occurring. The amount of sodium hypophosphite used is 2-8 times the molar ratio of nickel sulfate. By controlling the ratio of sodium hypophosphite to nickel sulfate, the phosphorus content in the Ni-P coating can be adjusted. The amount of sodium citrate used is 3-10% of the mass of the nickel sulfate, and the amount of thiourea used is 0.5-2% of the mass of the nickel sulfate. After the plating solution is prepared, the pH is adjusted to 12 with ammonia water, and glass powder 2.2 to 3.5 times the mass of nickel sulfate is weighed and added to the plating solution. It is heated to 90°C and reacted at a constant temperature for 1.5 hours while stirring to obtain a uniform and stable Ni-P coating. The coating thickness and quality are adjusted by controlling the amount of glass powder used.

[0035] In some more specific embodiments, the method for preparing the modified glass powder for the front silver paste of solar cells includes:

[0036] (1) Weigh the raw materials according to the ratio of each oxide in the glass frit and mix them in a mixer for 1 hour;

[0037] (2) Use a platinum crucible to load the mixed raw materials, place it in a muffle furnace, heat it to 1100°C, and keep it warm for 60 minutes;

[0038] (3) pouring the melt in the crucible onto a roller mill for cold rolling to obtain glass fragments;

[0039] (4) The glass fragments and zirconia balls with diameters of 10 mm and 5 mm were placed in a ball mill at a ratio of 1:3, and ball milled at a speed of 150 revolutions per minute for 24 hours. The resulting glass material was then filtered and dried.

[0040] (5) Weigh nickel sulfate and prepare a nickel sulfate solution with a concentration of 0.05 mol / L to 0.5 mol / L

[0041] (6) Weighing sodium hypophosphite in an amount 2 to 8 times the molar amount of nickel sulfate and dissolving it in the nickel sulfate solution;

[0042] (7) Weighing sodium citrate at 3% to 10% of the mass of nickel sulfate and weighing thiourea at 0.5% to 2% of the mass of nickel sulfate, and dissolving them in the nickel sulfate solution;

[0043] (8) Weighing glass powder 2.3 to 3.5 times the mass of nickel sulfate, adding it to the nickel sulfate solution, heating to 90°C while stirring, and reacting at this temperature for 1.5 hours;

[0044] (9) After centrifugation and washing to remove excess ions, the desired surface-modified glass powder is obtained.

[0045] The Ni-P modified glass powder of the present invention has excellent stability and greatly improved acid and alkali corrosion resistance, effectively preventing active groups on the surface of the glass powder from directly contacting the organic phase in the slurry, thereby improving the stability of the slurry. The viscosity of the slurry is relatively stable during dynamic printing and static storage, and there is no significant increase in viscosity or even the phenomenon of the slurry becoming sticky and hard. The melting point of the Ni-P alloy coating is between 800 and 1200° C., which is much higher than the softening point of the glass powder. This can prevent the glass powder from softening prematurely and flowing to the surface of the silicon wafer, reduce the degree of corrosion of the glass powder on the PN junction, and improve the open-circuit voltage of the solar cell. In addition, due to the good conductivity of the alloy coating, the electronic conductivity is increased, so that the solar cell has a better conversion efficiency.

[0046] Another aspect of the embodiments of the present invention further provides a solar cell front silver paste, which includes the aforementioned modified glass powder for solar cell front silver paste.

[0047] The modified glass powder used in the solar cell front silver paste increases the paste viscosity stability, reduces the printed grid breakage ratio, improves the solar cell open circuit voltage, improves the glass electronic conductivity, and improves the solar cell fill factor.

[0048] The technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments. This embodiment is implemented on the premise of the technical solution of the invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0049] Unless otherwise specified, the experimental materials used in the following examples can be purchased from conventional biochemical reagent companies.

[0050] Example 1

[0051] A modified glass powder for silver paste on the front side of a crystalline silicon solar cell. The glass powder comprises, using an oxide molar percentage technology, 20% SiO2, 30% TeO2, 18% PbO, 7% Bi2O3, 10% Li2O, 1% Na2O, 5% WO3, 5% ZnO, 2% MoO3, 1% CuO, and 1% MgO. The surface of the glass powder is coated with a Ni-P alloy coating having a mass percentage of 0.5%, wherein the mass percentage of P in the alloy coating is 4.8%.

[0052] The steps of preparing the composite glass powder in this embodiment are as follows:

[0053] (1) Weigh the raw materials according to the ratio of each oxide in the glass frit and mix them in a mixer for 1 hour;

[0054] (2) Use a platinum crucible to load the mixed raw materials, place it in a muffle furnace, heat it to 1100°C, and keep it warm for 60 minutes;

[0055] (3) pouring the melt in the crucible onto a roller mill for cold rolling to obtain glass fragments;

[0056] (4) The glass fragments and zirconia balls with diameters of 10 mm and 5 mm were placed in a ball mill at a ratio of 1:3, and ball milled at a speed of 150 revolutions per minute for 24 hours. The resulting glass material was then filtered and dried.

[0057] (5) Weigh nickel sulfate and prepare a nickel sulfate solution with a concentration of 0.05 mol / L

[0058] (6) Weighing sodium hypophosphite at 3 times the molar number of nickel sulfate and dissolving it in the nickel sulfate solution;

[0059] (7) Weighing sodium citrate at 5% of the mass of nickel sulfate and weighing thiourea at 1.5% of the mass of nickel sulfate, dissolving them in the nickel sulfate solution, and adjusting the pH to 12;

[0060] (8) Weigh glass powder 3.5 times the mass of nickel sulfate, add it to the nickel sulfate solution, heat it to 90°C while stirring, and keep the reaction at this temperature for 1.5 hours;

[0061] (9) After centrifugation and washing to remove excess ions, the desired surface-modified glass powder is obtained.

[0062] Example 2

[0063] A modified glass powder for silver paste on the front surface of a crystalline silicon solar cell, wherein the glass powder is the glass powder prepared in Example 1; the surface of the glass powder is coated with a Ni-P alloy coating with a mass percentage of 3%, wherein the mass percentage of P in the alloy coating is 5.5%.

[0064] The steps of preparing the composite glass powder in this embodiment are as follows:

[0065] (1) Weigh nickel sulfate and prepare a nickel sulfate solution with a concentration of 0.4 mol / L

[0066] (2) Weighing sodium hypophosphite at 4 times the molar number of nickel sulfate and dissolving it in the nickel sulfate solution;

[0067] (3) Weighing sodium citrate at 6.3% of the mass of nickel sulfate and weighing thiourea at 1.8% of the mass of nickel sulfate, dissolving them in the nickel sulfate solution, and adjusting the pH to 12;

[0068] (4) Weigh glass powder 2.7 times the mass of nickel sulfate, add it to the nickel sulfate solution, heat it to 90°C while stirring, and keep the reaction at this temperature for 1.5 hours;

[0069] (5) After centrifugation and washing to remove excess ions, the desired surface-modified glass powder is obtained.

[0070] Example 3

[0071] A modified glass powder for silver paste on the front side of a crystalline silicon solar cell. The glass powder comprises, using an oxide molar percentage technology, 28% SiO2, 20% TeO2, 15% PbO, 8% Bi2O3, 8% Li2O, 2% Na2O, 9% WO3, 4% ZnO, 3% MoO3, 1.5% CuO, and 1.5% MgO. The surface of the glass powder is coated with a Ni-P alloy coating having a mass percentage of 5%, wherein the mass percentage of P in the alloy coating is 6.4%.

[0072] The steps of preparing the composite glass powder in this embodiment are as follows:

[0073] (1) Weigh the raw materials according to the ratio of each oxide in the glass frit and mix them in a mixer for 1 hour;

[0074] (2) Use a platinum crucible to load the mixed raw materials, place it in a muffle furnace, heat it to 1100°C, and keep it warm for 60 minutes;

[0075] (3) pouring the melt in the crucible onto a roller mill for cold rolling to obtain glass fragments;

[0076] (4) The glass fragments and zirconia balls with diameters of 10 mm and 5 mm were placed in a ball mill at a ratio of 1:3, and ball milled at a speed of 150 revolutions per minute for 24 hours. The resulting glass material was then filtered and dried.

[0077] (5) Weigh nickel sulfate and prepare a nickel sulfate solution with a concentration of 0.5 mol / L

[0078] (6) Weighing sodium hypophosphite at 5.5 times the molar number of nickel sulfate and dissolving it in the nickel sulfate solution;

[0079] (7) Weighing sodium citrate at 6% of the mass of nickel sulfate and weighing thiourea at 2% of the mass of nickel sulfate, dissolving them in the nickel sulfate solution, and adjusting the pH to 12;

[0080] (8) Weigh glass powder 2.5 times the mass of nickel sulfate, add it to the nickel sulfate solution, heat it to 90°C while stirring, and keep the reaction at this temperature for 1.5 hours;

[0081] (9) After centrifugation and washing to remove excess ions, the desired surface-modified glass powder is obtained.

[0082] Example 4

[0083] A modified glass powder for silver paste on the front side of a crystalline silicon solar cell. The glass powder comprises, using an oxide molar percentage technology, 35% SiO2, 18% TeO2, 19% PbO, 5% Bi2O3, 4% Li2O, 2% Na2O, 12% WO3, 2% ZnO, 1% MoO3, 0.5% CuO, and 1.5% MgO. The surface of the glass powder is coated with a Ni-P alloy coating having a mass percentage of 4.2%, wherein the mass percentage of P in the alloy coating is 10.5%.

[0084] The steps of preparing the composite glass powder in this embodiment are as follows:

[0085] (1) Weigh the raw materials according to the ratio of each oxide in the glass frit and mix them in a mixer for 1 hour;

[0086] (2) Use a platinum crucible to load the mixed raw materials, place it in a muffle furnace, heat it to 1100°C, and keep it warm for 60 minutes;

[0087] (3) pouring the melt in the crucible onto a roller mill for cold rolling to obtain glass fragments;

[0088] (4) The glass fragments and zirconia balls with diameters of 10 mm and 5 mm were placed in a ball mill at a ratio of 1:3, and ball milled at a speed of 150 revolutions per minute for 24 hours. The resulting glass material was then filtered and dried.

[0089] (5) Weigh nickel sulfate and prepare a nickel sulfate solution with a concentration of 0.4 mol / L

[0090] (6) Weighing sodium hypophosphite at 8 times the molar number of nickel sulfate and dissolving it in the nickel sulfate solution;

[0091] (7) Weighing sodium citrate at 7% of the mass of nickel sulfate and weighing thiourea at 2% of the mass of nickel sulfate, dissolving them in the nickel sulfate solution, and adjusting the pH to 12;

[0092] (8) Weigh glass powder 2.7 times the mass of nickel sulfate, add it to the nickel sulfate solution, heat to 90°C while stirring, and keep the reaction at this temperature for 1.5 hours;

[0093] (9) After centrifugation and washing to remove excess ions, the desired surface-modified glass powder is obtained.

[0094] Example 5

[0095] A modified glass powder for silver paste on the front side of a crystalline silicon solar cell. The glass powder comprises, using an oxide molar percentage technology, 11% SiO2, 25% TeO2, 12% PbO, 12% Bi2O3, 8% Li2O, 4% Na2O, 15% WO3, 6% ZnO, 3% MoO3, 2% CuO, and 2% MgO. The surface of the glass powder is coated with a Ni-P alloy coating having a mass percentage of 1.5%, wherein the mass percentage of P in the alloy coating is 8.4%.

[0096] The steps of preparing the composite glass powder in this embodiment are as follows:

[0097] (1) Weigh the raw materials according to the ratio of each oxide in the glass frit and mix them in a mixer for 1 hour;

[0098] (2) Use a platinum crucible to load the mixed raw materials, place it in a muffle furnace, heat it to 1100°C, and keep it warm for 60 minutes;

[0099] (3) pouring the melt in the crucible onto a roller mill for cold rolling to obtain glass fragments;

[0100] (4) The glass fragments and zirconia balls with diameters of 10 mm and 5 mm were placed in a ball mill at a ratio of 1:3, and ball milled at a speed of 150 revolutions per minute for 24 hours. The resulting glass material was then filtered and dried.

[0101] (5) Weigh nickel sulfate and prepare a nickel sulfate solution with a concentration of 0.15 mol / L

[0102] (6) Weighing sodium hypophosphite at 6.4 times the molar number of nickel sulfate and dissolving it in the nickel sulfate solution;

[0103] (7) Weighing sodium citrate at 6% of the mass of nickel sulfate and weighing thiourea at 1.5% of the mass of nickel sulfate, dissolving them in the nickel sulfate solution, and adjusting the pH to 12;

[0104] (8) Weigh glass powder 3.1 times the mass of nickel sulfate, add it to the nickel sulfate solution, heat it to 90°C while stirring, and keep the reaction at this temperature for 1.5 hours;

[0105] (9) After centrifugation and washing to remove excess ions, the desired surface-modified glass powder is obtained.

[0106] Preparation of silver paste for the front side of a solar cell: 2.5 wt% of the modified glass powder prepared in Examples 1 to 5, 87.5 wt% of conductive silver powder, 3 wt% of polyvinyl butyral, 3 wt% of ethyl cellulose, 1 wt% of propylene glycol butyl ether acetate, and 3 wt% of ethylene glycol monobutyl ether acetate were mixed for 1 hour, the slurry was ground using a three-roll grinder, and the grinding fineness was tested using a scraper fineness tester. The grinding fineness of the slurry was less than 10 μm, thereby obtaining silver paste for the front side of a solar cell.

[0107] Table 1 Viscosity changes of silver pastes prepared from the modified glass frits described in Examples 1 to 5 and the ratio of printed broken grids

[0108] name Initial viscosity Viscosity after 7 days Viscosity increase Printing break ratio Commercial slurry 88.2 99.8 13.2% 1.22% Example 1 90.5 98.4 8.7% 0.68% Example 2 92.1 96.3 4.6% 0.41% Example 3 89.7 91.4 1.9% 0.12% Example 4 88.5 91.8 3.7% 0.22% Example 5 91.2 97.5 6.9% 0.55%

[0109] Table 2 Performance of silver paste prepared using the modified glass frits described in Examples 1 to 5 in solar cells

[0110] name Open circuit voltage / V Short-circuit current / A Fill factor / % Conversion efficiency / % Commercial slurry 0.6853 11.326 81.80 23.161 Example 1 0.6855 11.331 81.83 23.191 Example 2 0.6861 11.328 81.85 23.215 Example 3 0.6872 11.319 81.89 23.252 Example 4 0.6868 11.328 81.96 23.281 Example 5 0.6858 11.334 81.91 23.233

[0111] By comparing Examples 1 to 5 with commercial slurries, the viscosity growth of the slurries of Examples 1 to 5 after 7 days of placement is smaller than that of the commercial slurries, and the proportion of broken gates that appear in printing is also significantly reduced compared to the commercial slurries. In addition, Examples 1 to 5 show higher open circuit voltage and fill factor than the commercial slurries. Comparing Example 1 with Example 2, and Examples 3 to 5, as the content of Ni-P alloy in the surface modification of the glass powder increases, its effect of preventing the glass surface from directly contacting the organic phase is better, the viscosity growth is lower, the proportion of broken gates in printing is also smaller, and the electrical performance is manifested as a higher open circuit voltage. By comparing Example 1 with Example 5, and Example 2 with Example 4, when the quality of the Ni-P alloy coating is not much different, the higher the P content in the coating, the higher the fill factor in the electrical performance, and the higher the conversion efficiency of the solar cell.

[0112] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments using other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.

[0113] It should be understood that the technical solution of the present invention is not limited to the above-mentioned specific implementation cases. Any technical variations made according to the technical solution of the present invention without departing from the scope of protection of the purpose of the present invention and the claims shall fall within the scope of protection of the present invention.

Claims

1. A solar cell front silver paste, characterized in that: The invention comprises a modified glass powder for a front silver paste of a solar cell; the modified glass powder for the front silver paste of a solar cell comprises a glass powder and a Ni-P alloy coating coated on the surface of the glass powder, wherein the content of the Ni-P alloy coating in the modified glass powder for the front silver paste of a solar cell is 0.5-5wt%; the Ni-P alloy coating is coated on the surface of the glass powder by chemical plating; The method for preparing the modified glass powder for the front silver paste of solar cells comprises: The glass powder is placed in a plating solution containing a nickel salt, a reducing agent, a complexing agent and a stabilizer, and the reaction is stirred at 90° C. for 1.5 hours, and a Ni-P alloy coating is coated on the surface of the glass powder, so as to prepare a modified glass powder for the front silver paste of a solar cell, wherein the pH value of the plating solution containing the nickel salt, the reducing agent, the complexing agent and the stabilizer is adjusted to 12 by using ammonia water; the nickel salt is selected from nickel sulfate; the reducing agent is selected from sodium hypophosphite; the complexing agent is selected from sodium citrate; and the stabilizer is selected from thiourea; The concentration of nickel salt in the plating solution comprising nickel salt, reducing agent, complexing agent and stabilizer is 0.05~0.5 mol / L; the molar ratio of the reducing agent to the nickel salt is 2~8:1; the mass ratio of the stabilizer to the nickel salt is 0.5~2:100; the mass ratio of the complexing agent to the nickel salt is 3~10:100; and the mass ratio of the glass powder to the nickel salt is 2.2~3.5:

1.

2. The solar cell front silver paste according to claim 1, characterized in that: The glass powder is composed of three or more elements of Te, Pb, Bi, Li, Na, W, Si, Zn, Mo, Cu, Mg, Al, B, Ti, and Zr.

3. The solar cell front silver paste according to claim 1, characterized in that: The glass powder includes the following components counted by molar percentage of oxides: 5~50% SiO2, 5~40% PbO, 0.5~10% CuO, 5~40% TeO2, 5~15% Bi2O3, 1~10% Li2O, 1~5% Na2O, 5~20% WO3, 1~10% ZnO, 1~10% MoO3 and 1~5% MgO.

4. The solar cell front silver paste according to claim 1, characterized in that: The glass powder includes a skeleton support as a glass network structure and an intermediate and / or network modifier as a glass network structure; the skeleton support includes SiO2 and TeO2; the intermediate and / or network modifier includes PbO, CuO, Bi2O3, Li2O, Na2O, WO3, ZnO, MoO3 and MgO.

5. The solar cell front silver paste according to claim 1, characterized in that: The content of P in the Ni-P alloy coating accounts for 4-12wt% of the total coating.

Citation Information

Patent Citations

  • Nickel-coated glass conductive powder for electro-conductive rubber and preparation method thereof

    CN103871540A